Two new species of the genus Potentilla (Rosaceae) from North of Iran - Naqinezhad, Alireza; Faghir, Marzieh Beygom (Phytotaxa, 2019)
Potentilla sangedehensis and Potentilla diversidentata are two new species collected from high montane areas of Sangedeh, Central Hyrcanian region, North of Iran. The former is related to the representatives of the section Curvisetae especially P. collettiana, P.  curviseta and P. pteropoda   and the later can be classified in the section Persicae, the most species–rich section in Iran. Detailed morphological descriptions of the new species, their photographs, and comparison of diagnostic traits with allied species are provided.